(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This article examines the syncretism between Sufism and folk oral tradition in Transoxiana and its impact on the formation of religious and spiritual values. By analyzing historical sources and scholarly research, the study finds that Sufi teachings merged with local folklore, customs, and oral literature to disseminate Islamic ideas among the populace. Sufi concepts were popularized through folk songs, epic tales, and saint legends. Consequently, Islamic spiritual values became firmly rooted in the cultural soil of the region, fostering virtues such as moral purity, love of the divine, humility, and social harmony in the community.